Psychological functioning of drivers who present risky driving behavior and drive under influence of alcohol - Rzeszutko, Ewa (Current Problems of Psychiatry, 2013)
The purpose of this article is to depict psychological functioning of people who present risky and drunken driving. Police statistics indicate two specific groups of drivers causing accidents. The first group is composed of adolescents whose way of functioning is explained further from the perspective of Jessors’ problem behavior theory. The second group comprises individuals repeatedly sentenced for driving while intoxicated. Many studies on these groups involved multiple factor analysis undertaken in order to determine correlation between social, behavioral, and psychological factors.